LIABILITY FOR COMPENSATION ON HOSPITALS DUE TO HEALTH WORKFORCE NEGLIGENCE (A CRITIQUE) - Dhanudibroto, Handojo (International Journal of Social Service and Research, 2025)
This research examines the implications of Article 193 of Law No. 17 of 2023 concerning Health, which imposes sole liability on hospitals for negligence by health workers. This provision raises concerns about fairness and justice, as it deviates from established principles of shared accountability in Indonesian civil law. The study aims to critique this legal framework, assess its alignment with international standards, and explore its impact on healthcare delivery. Using a descriptive method, the research analyzes legal documents, case law, and relevant literature to understand the complexities of liability in healthcare. The findings reveal that Article 193 undermines the principles of distributive, retributive, and compensatory justice, potentially eroding trust in the legal system and discouraging hospitals from providing high-risk services. Furthermore, the study highlights that this one-sided liability can create an adversarial relationship between hospital management and health workers, ultimately harming patient care. The implications of this research suggest the need for legal reforms that promote shared accountability among healthcare providers and individual practitioners. By advocating for a reassessment of Article 193, the study aims to inform policymakers and legal professionals on creating a balanced liability framework that fosters a collaborative healthcare environment and enhances patient safety.